Self-rated health, work characteristics and health related behaviours among nurses in Greece: a cross sectional study - Dimoliatis Ioannis DK; Alamanos Yannis; Pappas Noula A (BMC, 2005)
Abstract Background Previous studies on self-rated health among nurses have indicated an association of low job satisfaction and stress in relation to poor self-rated health. The relationship between self rated health and the specific work characteristics and health related behaviours of nurses to our knowledge have not been adequately studied. Objective To investigate the health profile of nurses working in hospitals in North West Greece and to examine the associations between self rated health (SRH) and health related behaviours and work characteristics in this group of hospital employees. Methods A self-administered questionnaire was distributed to a random sample of 443 nurses working in all the hospitals in North West Greece. Regression analysis was used to examine the relationship of health related behaviours and work characteristics with self rated health among the nurses. Results A total of 353 responded to the questionnaire (response rate 80%) of which 311 (88%) were female and 42 (12%) male. The mean age (standard deviation) of the respondents was 36 years (5.6) and their mean years of working as nurses were 13.5 years (5.9). Almost half of the nurses' smoked, and about one third were overweight or obese. About 58% (206) of the nurses reported having poor health while 42% (147) reported having good health. Self-rated health was independently associated with gender, effort to avoid fatty foods and physical activity, according to multiple logistic regression analysis. Conclusion The population studied presented a relatively poor health profile, and a high proportion of poor SRH. Though female gender and effort to avoid fatty foods were associated with poor SRH, and exercise and white meat consumption with good SRH, specific work characteristics were not associated with SRH.